2022
DOI: 10.1186/s13033-022-00548-5
|View full text |Cite
|
Sign up to set email alerts
|

Brief interventions for alcohol use disorders in low- and middle-income countries: barriers and potential solutions

Abstract: Global alcohol consumption and harmful use of alcohol is projected to increase in the coming decades, and most of the increase will occur in low- and middle-income countries (LMICs); which calls for cost-effective measures to reduce alcohol exposure in these countries. One such evidence based measure is screening and brief intervention (BI) for alcohol problems. Some of the characteristics of BI make them a particularly appealing choice of interventions in low-resource settings. However, despite evidence of ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…The first example is taken from Davis et al (2016) who demonstrated an association between a longer DUP and the use of amphetamines or Mandrax. Substance use disorders are prevalent public health problems in LMICs (Sarkar et al, 2021) and are projected to increase in coming years (Nadkarni et al, 2022). Given that substance use and psychosis are common co‐occurring disorders (Davis et al, 2016), brief psychosocial interventions to target substance use in LMICs (WHO, 2016) may be useful potential strategies for DUP reduction.…”
Section: Discussionmentioning
confidence: 99%
“…The first example is taken from Davis et al (2016) who demonstrated an association between a longer DUP and the use of amphetamines or Mandrax. Substance use disorders are prevalent public health problems in LMICs (Sarkar et al, 2021) and are projected to increase in coming years (Nadkarni et al, 2022). Given that substance use and psychosis are common co‐occurring disorders (Davis et al, 2016), brief psychosocial interventions to target substance use in LMICs (WHO, 2016) may be useful potential strategies for DUP reduction.…”
Section: Discussionmentioning
confidence: 99%
“…SMS employs text messages to provide people who use drugs with useful information regarding harm reduction, treatment adherence and/or social support as well as selfmonitoring opportunities [15]. These EBIs have been evaluated largely in high-income countries in North America or North Europe [9,10] but have limited empirical evidence of their impact in low-and-middle-income countries where the available qualified workforce for substance use treatment is inadequate to the needs of the population [19,20]. In both resource-rich and resourceconstrained settings, however, there is a need to identify how best to combine these EBIs to ensure optimal and cost-effective treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Mental health and AUD are poorly studied in many low-and middle-income countries (LMICs), with few resources and trained personnel available to treat disorders that arise within the general population (17)(18)(19). This healthcare gap is especially concerning given that alcohol use and AUD are rising in LMICs (12,(20)(21)(22). For example, there are only 55 psychologists and psychiatrists in Tanzania, a nation of more than 63 million people (23).…”
Section: Introductionmentioning
confidence: 99%